A strategy for the execution of copy and delete operations in the tree of objects - A. V. Mayorov (Моделирование и анализ информационных систем, 2011)
The paper discusses some general rules for organizing database objects into hierarchical structures. It describes different kinds of relations between objects, and the role that relations play in the organization of such structures. It also defines principles of executing object copy and delete operations that do not break the logic of relations between objects.